On electron boundary conditions in PIC plasma thruster plume simulations. (27th March 2019) - Li, Min; Merino, Mario; Ahedo, Eduardo; Tang, Haibin
Abstract: The collisionless, steady state expansion of a warm electron, cold ion plasma thruster plume into vacuum is studied with an electrostatic particle-in-cell model and globally-consistent boundary conditions that discriminate between reflected and escaping electrons. As a proof of concept, several simulations are analyzed. Results from both two-dimensional planar and axisymmetric plasma plumes are discussed. In particular, the electron anisothermal and anisotropic behavior in the plume is recovered.